Filial Piety in Imperial China - Simanavičiūtė, Ieva (Acta Orientalia Vilnensia, 2004)
The concept of filial piety is not only a philosophical idea, but also a practical rule of ethics, which has persisted to the present time and is clearly reflected in nowadays’ societies of East Asia. The aim of this article, concerning filial piety in imperial China, is to reveal the peculiarities of and the consensuses and contradictions in the conception and interpretation of filiality in Orthodox Confucianism and popular practices, as well as in Buddhism and Daoism. The study is a novelty in Lithuanian sinology as it offers a wide view on the subject, discovering its manifestations in all the three main teachings. It is an exploratory work of original sources, with some references to available studies of Western scholars. It concludes by saying that filial piety found its prominent place in most of the teachings and certainly made a great impact on nowadays’ East Asian cultures.